Self-reported voice problems in call center employees during the COVID-19 pandemic: prevalence, risk factors, and occupational conditions - Songul Demir; Bilal Sizer; Sehmus Yildiz (PeerJ, 2025)
Background The COVID-19 pandemic has significantly altered work environments, especially for call center employees (CCEs), who face increased vocal strain due to prolonged speech, stressful conditions, and changes in work dynamics. This study aims to assess the prevalence of self-reported voice problems among CCEs during the pandemic, focusing on the influence of occupational factors, psychosocial stress, and demographic variables on vocal health. Methods A cross-sectional survey was conducted with 264 CCEs in Turkey between September 2021 and October 2021 during the pandemic. Participants were individuals who had worked in a call center for at least 6 months, were 18 years or older, had no psychiatric diagnoses, and voluntarily consented to participate; those with a history of voice disorders or vocal cord surgery were excluded. Participants completed a demographic questionnaire and the Voice Handicap Index–Short Form (VHI-SF), a validated tool for measuring the impact of voice disorders on quality of life. Descriptive statistics and non-parametric tests were applied to examine the relationships between workers’ characteristics, work conditions, and voice disorder scores. Results The study sample was comprised of 72% women, with a median age of 25 years (IQR: 22–28). The prevalence of voice disorders was found to be 57.6%. Key risk factors for elevated VHI-SF scores included working more than 8 h daily, having over 5 years of experience, experiencing high stress, and exhibiting poor posture. Workers with inadequate knowledge of proper voice usage or those reporting throat irritation had significantly higher VHI-SF scores. Additionally, those who used their voices for more than 5 h per day, had respiratory allergies, or reported poor vocal health, also exhibited higher VHI-SF scores. No significant correlation was observed between VHI-SF scores and gender, education level, smoking habits or hydration. Conclusion The study highlights the high prevalence of self-reported voice problems among CCEs during the pandemic and identifies several key occupational and psychosocial risk factors. Interventions targeting voice care education, stress management, and ergonomic work conditions may be beneficial in reducing the incidence and severity of voice disorders in this population.